The Use of Peer Tutoring Strategies to Enhance Learning Motivation in Islamic Education - Amelia Putri Adiana; Muhammad Azamuddin Syahapala; Ayok Ariyanto; Azid Syukroni (Tahta Media Group, 2026)
This study examined the use of peer tutoring strategies to enhance students’ learning motivation in Islamic Education (PAI: Pendidikan Agama Islam). Conventional lecture-based pedagogy often positions students as passive learners, which may reduce engagement and limit the development of critical thinking. This research aimed to analyze the implementation of peer tutoring and evaluate its impact on students’ learning motivation. This study employed a qualitative case study approach conducted in a vocational high school. Data were collected through classroom observations, in-depth interviews with teachers and students, and documentation analysis. The data were analyzed using data reduction, data display, and conclusion-drawing techniques to ensure systematic interpretation. The findings revealed that peer tutoring had a positive impact on students’ learning motivation. Effective implementation was supported by structured planning, including tutor selection and adaptation to students’ learning characteristics. Increased motivation was reflected in higher participation, enthusiasm, and improved peer interaction. Additionally, students who acted as tutors demonstrated enhanced self-efficacy and confidence. These improvements contributed to better learning outcomes in Islamic education. The originality of this study lies in its focus on peer tutoring within the context of Islamic education, which remains underexplored. However, this study was limited to a single research setting and a qualitative approach, which may restrict the generalizability of the findings.